Would the Accuracy of Dental Apex Locators in Determining the Apical Constriction be Influenced by the Activation Sequence? An Ex vivo Study - , Mirlyn de Souza Dias; , Mayra Rolim Alencar; , Suyane Maria Luna-Cruz; , Joana Lia Freitas Furtado; , Maria Aline Ferreira Damasceno; , Alinne Patierry Oliveira Pacífico Feitosa; , Elilton Cavalcante Pinheiro Júnior; , Nilton Vivacqua Gomes; , Bruno Carvalho de Vasconcelos (Archives of Current Research International, 2025)
Aims: To evaluate the accuracy of three electronic foraminal locators (EFLs) – Root ZX II, Propex Pixi, and Romiapex A-15 – when used in different activation sequences, focusing on the influence of these sequences on the working length determination. Study Design: Experimental study conducted in a laboratory setting using extracted human teeth. Methodology: Thirty single-rooted human teeth with standardized apical foramina were used to assess the accuracy of the EFLs. Measurements were taken after canal preparation and determination of the RCL with the aid of a digital caliper. The devices were tested in four activation sequences: DA/LC/FC/FI, DA/LC/FI/FC, LC/DA/FC/FI, and LC/DA/FI/FC. The EFL measurements were compared with the manually determined RCL, and results were analyzed using non-parametric statistical tests. Results: No significant differences were observed between the devices across the different activation sequences (P > 0.05). However, the Root ZX II showed the lowest mean error (0.13 mm) in the DA/LC/FC/FI sequence, performing better than the other devices (P < 0.05). Conclusion: The activation sequence of EFLs did not significantly influence measurement accuracy. However, the DA/LC/FC/FI sequence favored the accuracy of the Root ZX II, suggesting that this sequence may be the most effective for this device.